Management Of Distance Learning Programs In Bengkulu Junior High Schools (Lembaga Pengembangan Kinerja Dosen, 2023)
In order to boost participation and encourage student participation in homeschooling activities in SMPN 1 Bengkulu, this research aims to: establish plans and regulations; move; control; check the effectiveness of implementation; and remove any barriers that arise during that process. This study employs documentary techniques, observations, and interviews to conduct a qualitative descriptive study. The researchers will investigate and determine whether or not the management of the PJJ program has been implemented successfully. Kushendar model analysis was employed. Data is reduced, presented, concluded from, and verified by researchers. The conclusion is as follows, based on data analysis: (1) Planning is done by creating operational work plans and objectives. (2) Methods for regulating the use of resources, methods for socializing the work plan, and mechanisms for regulating the execution of a work plan that go along with the delegation of tasks and powers are established.